Teachers' attitudes towards the use of ICTs for teaching business studies in Soshanguve secondary schools - Mihai, Maryke Anneke (University of Pretoria, 2025)
Dissertation (MEd (Science, Mathematics and Technology Education))--University of Pretoria, 2024.